2012
DOI: 10.1002/pssb.201084221
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of solitary waves in a common or auxetic elastic rod with both quadratic and cubic nonlinearities

Abstract: Results of numerical simulations are presented for propagation of solitary waves in an elastic rod of positive or negative Poisson's ratio, i.e. of a common or auxetic material. Splitting of various initial pulses during propagation into a sequence of solitary waves is considered in frames of a model which contains both quadratic and cubic nonlinear terms. The obtained results are compared with some exact analytic solutions, called solitons, what leads to the conclusion that the solitons describe well the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…It has been shown that these soliton solutions approximate very well numerical results obtained for various forms of initial pulses. Present considerations confirm the earlier result [20] that special exact solutions can be very useful for predicting more complicated solitary waves obtained by numerical simulations. The simulations showed also that the averaged amplitudes and velocities of solitary waves increase monotonically with the Poisson's ratio.…”
Section: Figuresupporting
confidence: 90%
See 2 more Smart Citations
“…It has been shown that these soliton solutions approximate very well numerical results obtained for various forms of initial pulses. Present considerations confirm the earlier result [20] that special exact solutions can be very useful for predicting more complicated solitary waves obtained by numerical simulations. The simulations showed also that the averaged amplitudes and velocities of solitary waves increase monotonically with the Poisson's ratio.…”
Section: Figuresupporting
confidence: 90%
“…Closing this section it is worth to stress that, as it was found earlier in other systems , both the velocity and amplitude of solitons are increasing functions of Poisson's ratio.…”
Section: Numerical Simulationssupporting
confidence: 52%
See 1 more Smart Citation
“…Auxetic materials have potential applications, including in the aerospace industry , textile fabrics , and bioprostheses , among others . There has been numerous experimental , theoretical , and simulation studies to investigate the auxeticity of materials. Approximately 70% of the known cubic materials show a negative Poisson's ratio along the [1true1¯0] direction when they are stretched along the [110] direction .…”
Section: Introductionmentioning
confidence: 99%
“…In [12][13] authors found soliton solution of non-linear partial differential equations using analytical and numerical methods. The F-expansion method is also one of the most useful methods for finding analytical solutions of non-linear partial differential equations [14].…”
Section: Introductionmentioning
confidence: 99%